The Effect of Leadership on Work Stress at PT. Karya Anugerah Bersama Permai (PT. KABP) - Niarita Bukit (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the influence of leadership on work stress and to analyze the influence of leadership on work stress at PT. Karya Anugerah Bersama Permai (PT. KABP). The type of research used in this research is explanatory research using a quantitative approach. The population and sample in this study were all employees who worked at PT. Karya Anugerah Bersama Permai (PT. KABP) totaling 36 people. The analytical technique used is descriptive statistical analysis. The results of research conducted with SPSS 20.0 indicate that leadership has a significant influence on work stress as evidenced by a partially significant test (t test) with a significance value obtained 0.00 < 0.05 and a t value of t table 1.69, namely the t-count value of leadership is 11,053. The results of simple linear regression coefficients, obtained the equation Y = 3.389 + 1.050X with an R Square value of 0.782 so it can be concluded that the leadership variable has a positive and significant influence of 78.2% on work stress, while the remaining 21.8% is influenced by factors other.